Comments on A case study on engineering failure analysis of link chain - George Y.H. Yu (Elsevier, 2021)
The article by Tae-Gu Kim et al. conducted elastic FE modeling, which was inappropriate for fracture of elastic-plastic chain material (11.3% of elongation). FE analysis results and the findings in the fractographic analysis did not tally but contradicted each other. The article identified "incorrect installation"/ bending forces as the root cause while FE results of the chain under bending forces showed very low stresses at fracture locations but the highest stress in the middle of shank of the chain. The article's "step-like topographies indicating the fracture due to bending moment rather than uniaxial tension" lacked scientific support. The load value carried by each chain section under bending/incorrect installation was only half of that under tension, thus the article using same load value in FE simulation comparison for bending and tension was incorrect. The real cause of the chain fracture was likely improper checking the lifted load or/and using the wrong chain with much lower safety working load.